Regional Variations in Attitudes Towards Refugees: Evidence from Great Britain - Heaven Crawley; Stephen Drinkwater; Rukhsana Kauser (Institute for the Study of Labor (IZA), 2013)
This paper examines changes in public attitudes towards refugees across Britain over almost three decades using data from British Social Attitudes Surveys. It therefore covers the period when immigration as a whole has increased and the number of asylum applications reached their highest levels. The data are examined in periods before and after the rise in asylum applications and from a sub-national perspective because of possible differences in attitudes between areas, as well as in levels and types of inward migration. Overall, the British public appear to have become less tolerant towards refugees. This suggests that rising levels of immigration and asylum, a political discourse which positioned asylum as a particular problem in terms of the management of migration flows and accompanying press coverage have resulted in a hardening of opinions. These changes have occurred despite increased educational attainment amongst the British population, which might be expected to result in more liberal attitudes. The sub-national analysis indicates that people living in London and Scotland display the most tolerant views both before and after the increase in immigration and asylum. However, characteristics such as belonging to an ethnic minority group or possessing a degree, which are higher in London, account for a large portion of the regional variations. Controlling for such factors in regression analysis reduces the differentials relative to London, especially in more recent years.
Keywords: F22; J15; R23; 330; public attitudes; regional variations; immigration; refugees